KUSTOMISASI LINGKUNGAN RESTORAN UNTUK MAKAN DI TEMPAT (DINE-IN) DI ERA TATANAN KEHIDUPAN BARU - Muhammad Jimly Imamuddin; Mirwan Ushada (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
The Covid-19 pandemic in 2020 caused everything to change, including the pattern of human life. Currently, the activities carried out must comply with health protocols. Despite the restaurant's strict safety protocol measures, customers generally do not feel safe dine-in during a pandemic. This study classified the restaurant environment in the form of premium, deluxe, and standard classes using Kansei engineering. This study aimed to identify the attributes of an ergonomic environment in a restaurant for dine-in in the era of the post-pandemic era also find out the best alternative by Technique for Order Preference by Similiarity to Ideal Solution (TOPSIS). A total of 503 respondents from 3 provinces on the island of Java (East Java, Central Java, DI Yogyakarta) participated in the survey in this study. In detail, 41 respondents were needed for interviews, 418 respondents for attribute determination and 44 expert respondents for the TOPSIS. Kansei results generated 37 attributes in the premium, 39 attributes in the deluxe and 7 attributes in the standard classes. The research concluded that consumers tend to choose premium class facilities to dine-in at restaurants in the era of the new order of life. Keywords : dine-in, ergonomics, kansei engineering, TOPSIS